Association between Diabetes Mellitus and Multi-drug-resistant Tuberculosis: Evidence from a Systematic Review and Meta-analysis - Tegegne, Balewgizie Sileshi; Mengesha, Melkamu Merid; Teferra, Andreas A.; Awoke, Mamaru Ayenew; Habtewold, Tesfa Dejenie; Habtewold, Tesfa Dejenie (Springer, 2018)
Background Diabetes mellitus (DM) poses a significant risk for the development of active tuberculosis (TB) and complicates its treatment. However, there is inconclusive evidence on whether the TB-DM co-morbidity is associated with a higher risk of developing multi-drug-resistant tuberculosis (MDR-TB). The aim of this meta-analysis was to summarize available evidence on the association of DM and MDR-TB and to estimate a pooled effect measure. Methods PubMed, Excerpta Medica Database (EMBASE), Web of Science, World Health Organization (WHO), and Global Health Library database were searched for all studies published in English until July 2018 and that reported the association of DM and MDR-TB among TB patients. To assess study quality, we used the Newcastle-Ottawa Scale for cohort and case-control studies and the Agency for Healthcare Research and Quality tool for cross-sectional studies. We checked the between-study heterogeneity using the Cochrane Q chi-squared statistic and I.sup.2 and examined a potential publication bias by visual inspection of the funnel plot and Egger's regression test statistic. The random-effect model was fitted to estimate the summary effects, odds ratios (ORs), and 95% confidence interval (CIs) across studies. Results This meta-analysis of 24 observational studies from 15 different countries revealed that DM has a significant association with MDR-TB (OR = 1.97, 95% CI = 1.58-2.45, I.sup.2 = 38.2%, P value for heterogeneity = 0.031). The significant positive association remained irrespective of country income level, type of DM, how TB or DM was diagnosed, and design of primary studies. A stronger association was noted in a pooled estimate of studies which adjusted for at least one confounding factor, OR = 2.43, 95% CI 1.90 to 3.12. There was no significant publication bias detected. Conclusions The results suggest that DM can significantly increase the odds of developing MDR-TB. Consequently, a more robust TB treatment and follow-up might be necessary for patients with DM. Efforts to control DM can have a substantial beneficial effect on TB outcomes, particularly in the case of MDR-TB.
© The Author(s). 2018 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated. Systematic review registration PROSPERO CRD42016045692.
Keywords: Diabetes mellitus; Tuberculosis; Multi-drug-resistant tuberculosis; Systematic review; Meta-analysis